This is how I lied [large type] - Gudenkauf, Heather (Thorndike Press, 2020)
"Everyone has a secret they'll do anything to hide... Twenty-five years ago, the body of sixteen-year-old Eve Knox was found in the caves near her home in small-town Grotto, Iowa -- discovered by her best friend, Maggie, and her sister, Nola. There were a handful of suspects, including her boyfriend, Nick, but without sufficient evidence the case ultimately went cold. For decades Maggie was haunted by Eve's death and that horrible night. Now a detective in Grotto, and seven months pregnant, she is thrust back into the past when a new piece of evidence surfaces and the case is reopened. As Maggie investigates and reexamines the clues, secrets about what really happened begin to emerge. But someone in town knows more than they're letting on, and they'll stop at nothing to keep the truth buried deep." --